Factors associated with musculoskeletal disorders in cleaning workers of the emergency service of a tertiary hospital: Factores asociados a trastornos musculoesqueléticos en trabajadores de limpieza del servicio de emergencia de un hospital terciario - Zamora-Chávez, Sara C. (2020)
Introduction: Musculoskeletal disorders are health problems that can lead to disability. Objective: Todetermine the factors associated with the presence of musculoskeletal disorders in cleaning workers inthe emergency service of the Edgardo Rebagliati Martins National Hospital, 2019. Methods: Descriptive,observational, cross-sectional retrospective with a quantitative approach. The survey technique wasused and the instrument was the Standard Nordic Questionnaire. Descriptive and inferential statisticswere applied. Results: 129 participants, female (82.95%); median age 43 years, height 1.55m, overweightor obese (57.37%), secondary or higher education (93.80%), originating in the interior of the country(37.21%) and from Lima; 32 years lived in Lima, the median working time was 18 months, 43.41% workedin the morning and 9.30% worked in more than one place (9.30%). They presented musculoskeletal pain93.02%, pain in more than one area 75.97%, low back pain 65.12%, back pain 47.29%, neck pain (37.21%)and elbow / forearm pain 13, 18%. Only in the bivariate analysis, the working time was significant forthe presence of pain (p value=0.009). Conclusion: After performing the adjusted analysis, no factorsassociated with musculoskeletal disorders were found.